Complexity and Knowledge in Organisational Context: Concepts, Approaches, Boundaries and Relations - Jorge, Carlos Francisco Bitencourt [UNESP]; Valentim, Marta Lígia Pomim [UNESP]; Sutton, Michael J. D.; De Sordi, José Osvaldo (World Scientific Publishing, 2021)
The study sought to understand the relationship among organisations, knowledge and complexity so that managers could develop more effective strategies when working with organisational knowledge and complexity. The theoretical framework of the theme was elaborated from Web of Science and then an analysis of identified approximations, relations and boundaries was carried out. Aiming at greater consistency regarding the approximations and boundaries among the studied themes, we sought complex organisations that contemplated knowledge as a resource. The initial search retrieved 95 articles, and after content analysis was performed, we identified 25 articles considering complex organisations as social organisms and knowledge as a resource. In this sense, difficulties were observed regarding the definition of the concept of complex organisation, as well as regarding the understanding of knowledge as a resource. After the analysis of the 25 articles, eight pointed to some characteristic of complex organisations, and this corpus does now allow to relate and identify the impact of knowledge on complexity, or complexity on knowledge. From these considerations, we discuss ways to manage complexity and knowledge as elements inserted in the organisational context.
Keywords: complexity; Knowledge; knowledge management; organisations; resources; Content analysis; Organisational; Organisational knowledge; Theoretical framework; Web of Science